Pengaruh Buangan Krimer Nabati Sebagai Pupuk Terhadap Pertumbuhan Tanaman Sawi - Bukti; Yanatra Budi Pramana; Manik Ayu Titisari; Arif Yachya; Suparman; Nony Kezia Marchyta; Krisyanti Budipramana (Universitas PGRI Adi Buana Surabaya, 2026)
The vegetable creamer-based food industry produces a large amount of waste that has not been optimally utilized, reaching more than 1.4 tons per month and accumulating up to 17 tons in a period of 10 months. Disposal of this waste also requires considerable costs, so a more sustainable alternative utilization is needed. This study aims to assess the effect of applying vegetable waste creamer solution as liquid organic fertilizer on the growth and yield of mustard greens (Brassica rapa var. Parachinensis L.). The treatments used consisted of four solution compositions: 0% (control), 10%, 30%, and 50%. Parameters observed included plant height, number of leaves, and plant wet weight. The results showed that the treatment with 10% concentration gave the most optimal results on plant height and wet weight, while the highest number of leaves was obtained from the 0% treatment. High concentrations (30% and 50%) actually inhibited growth and caused plant death. These results indicate that waste creamer has potential as a liquid organic fertilizer if used in the right composition. Keyword: Vegetable Creamer, Industrial Waste, Organic Fertilizer